Strategic study on energy-protein requirements for local sheep: 5. Ewes during lactation phase - Mathius, I-W; Sastradipradja, D; Sutardi, T; Natasasmita, A; Sofyan, L.A; Sihombing, D.T.H (Indonesian Journal of Animal and Veterinary Sciences, 2003)
Thirty-six Javanese thin-tail ewes in the end of late pregnancy phase were set out to study the energy and crude protein requirements during the first eight-week of lactation phase. The ewes were penned individually in doors and randomly assigned to a 3 x 3 factorial arrangement, consisting of three levels of energy (low, medium and high) and three levels of crude protein (low, medium and high) diets with four ewes per treatment. The diets were pelleted and offered four times daily in approximately equal amount. Feed intake, nutrient digestibility, body weight and milk production were recorded. Results showed that, total lamb birth weights was not affected, but protein content on the ration treatments significantly altered (P<0.05) milk yield and composition. Dry matter intake due to feeding treatments was not significantly affected (P>0.05), while crude protein content on the ration highly significantly affected (P<0.01). Based on data recorded, the energy and protein requirements for ewes during lactation phase are highly significantly depended on ewesâ live weight, milk production and the ratio of energy metabolism and crude protein of the ration. It was concluded that in order to fulfil the crude protein and energy needs of the ewes during lactation phase, the ration given should contain crude protein and energy as much as 16% (based on dry matter) and 13.4 MJ/kg dry matter respectively. Â  Key words: Energy-protein requirement, lactation phase, local ewes Â